Growth of “shihuahuaco” Dipteryx ferrea (Ducke) Ducke in plantations under different spacings and soil types in Ucayali, Peruvian Amazon - Flores, Ymber (2025)
The results of experimental trials with Dipteryx ferrea (Ducke) Ducke, a forest species commonly known as "shihuahuaco", established under four different forest and agroforestry systems at the Alexander von Humboldt Experimental Center, Ucayali, at an altitude of 225 meters above sea level, are presented. These systems were differentiated by spatial arrangement, initial spacing, soil type, and were 11 years old. Measurements of total height, diameter at breast height (DBH), basal area, and timber volume of the plantations were obtained. The results demonstrate the growth potential, survival, and productivity of D. ferrea in both pure and mixed open-field plantations. System 1, on Plinthic acrisol soil, flat physiography, and 5 × 5 m spacing, showed the highest average DBH, total height, and dominant height, with values of 20.23 cm, 13.9 m, and 16.8 m, respectively. These results are statistically superior (p < 0.05) to those of other analyzed plantations and indicate promising performance. In terms of productivity, system 3, on Plinthic gleysol soil, flat physiography, and 2 × 2 m spacing, exhibited the highest values of basal area and roundwood volume, with 38.40 m2 /ha and 243.3 m3 /ha, respectively, statistically superior to the other systems, but also heavily influenced by the high plantation density. These findings suggest encouraging prospects for establishing D. ferrea plantations in forestry settings.